Gender Dichotomy of Board Members and Ownership Structure in Dividend Payout: A review - Anuar, Emma; Abd Aziz, Rozainun; Mohamad, Maslinawati; Hashim, Rugayah (Environment-Behaviour Proceedings Journal, 2020)
The purpose of the paper is to examine the effect between gender dichotomy and dividend payout. The objective of the paper is to provide adequate support for research through rigorous reviews of the literature on board dichotomy relative to gender and dividend payout. Board dichotomy of board members relative to gender seems to have a positive association with dividend payout. Ownership structure, especially institutional ownership, seems to have an association with dividend payout compared to other variables of ownership structure. The two corporate governance components have a monitoring role, can be a substitute or a tool for corporate governance improvement, and a signal to investors on dividend payout. Keywords: corporate environment; board composition; gender; dividend payout eISSN: 2398-4287 Â© 2020. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/e-bpj.v5i13.1954